Male Involvement in Spousal Reproductive Healthcare Services Utilization in Rivers State: An Application of the Theory of Planned Behaviour - Peter-Kio, Opirite Boma; David-West, Irene (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
This study investigated the determinants of male involvement in reproductive healthcare services utilization among men in Rivers State. Descriptive design was used. The population consisted of 2,670,903. Sample size was 1,200. The multi-stage sampling was used. Data was collected using questionnaire. A reliability co-efficient of 0.79. Data was collected by face-to-face delivery of questionnaire to the respondents. Mean, standard deviation and Pearson Correlation at 0.05 level of significance was used for data analysis. The result showed that there was very low non-significant relationship between perceived behavioural control and male involvement as p>0.05 (n = 1,167; r = 0.16; p = 0.09). Also, there was a moderate and non-significant relationship between behavioural intention and male involvement (n = 1,167; r = 0.41; p = 0.08). Furthermore, there was a low and non-significant relationship between subjective norm and male involvement as p>0.05 (n = 1,167; r = 0.34; p = 0.09). It was concluded that, male involvement in reproductive healthcare is determined by multiple factors. It was recommended that, public healthcare practitioners should give special attention to organizing campaigns targeted at men by collaborating with community health workers to involve men in reproductive healthcare; and Non-Governmental Organizations (NGOs) and Community Based Organizations (CBOs) should put more effort in disseminating reproductive healthcare information through campaigns to sustain good knowledge and improve on those with poor knowledge of reproduction to influence male involvement.